Using Case Studies to Investigate Cetacean Bycatch/Interaction Under-Reporting in Countries With Reporting Legislation - Charla Jean Basran; Guðjón Már Sigurðsson (Frontiers in Marine Science, 2021)
Accurate reporting of cetacean bycatch in/interaction with fishing gear in fisher logbooks would be of immense scientific value; however, despite some countries having mandatory reporting laws, logbook reporting is widely considered unreliable and cetacean catches are thought to be under-reported. Despite this widespread notion of logbook unreliability, under-reporting has rarely been quantified. For this study, initially we compiled the first comprehensive legislation summary for countries which have cetacean bycatch/interaction reporting laws. We then used data provided by government and research agencies in three case study countries (New Zealand, United States, and Iceland) to test for differences between logbook and observer reported cetacean bycatch. Comparisons were made using paired t-tests and Wilcoxon tests with a set alpha of 0.05. Overall, cetacean bycatch recorded by observers was higher than that from fisher logbooks by an average of 774% in trawls, 7348% in nets, and 1725% in hook and line gears. When combining all years of data available, fisher logbook cetacean catch per unit efforts or average number of individuals caught were significantly less than those from observer data for all gear types that could be examined in all countries, except for lining in New Zealand. Overall, there was significant under-reporting in the case study countries despite differences in geographic location, cetacean species and density and EEZ size, suggesting these results would likely be similar in many countries with comparable, well-developed fishing industries. Under-reporting in logbooks, despite laws, was clearly quantified and it is known that fishers have little incentive to report and have concerns over negative repercussions to the industry over bycatch issues. If logbook reporting is to continue in some fisheries, clearer legislation, simplified reporting using new technology (such as smartphone apps) and combination with electronic monitoring cameras to verify compliance may improve reporting accuracy. The introduction of electronic monitoring, given its lower cost compared to observer programs and high accuracy, may be the most viable option to obtain reliable cetacean bycatch estimates, and could be considered to replace logbook reporting altogether.